Lessons from helminth infections: ES‐62 highlights new interventional approaches in rheumatoid arthritis. (July 2014) - Pineda, M. A.; Al‐Riyami, L.; Harnett, W.; Harnett, M. M.
Summary Parasitic worms are able to survive in their mammalian host for many years due to their ability to manipulate the immune response by secreting immunomodulatory products. It is increasingly clear that, reflecting the anti‐inflammatory actions of such worm‐derived immunomodulators, there is an inverse correlation between helminth infection and autoimmune diseases in the developing world. As the decrease in helminth infections due to increased sanitation has correlated with an alarming increase in prevalence of such disorders in industrialized countries, this 'hygiene hypothesis' has led to the proposal that worms and their secreted products offer a novel platform for the development of safe and effective strategies for the treatment of autoimmune disorders. In this study we review the anti‐inflammatory effects of one such immunomodulator, ES‐62 on innate and adaptive immune responses and the mechanisms it exploits to afford protection in the murine collagen‐induced arthritis (CIA) model of rheumatoid arthritis (RA). As its core mechanism involves targeting of interleukin (IL)‐17 responses, which despite being pathogenic in RA are important for combating infection, we discuss how its selective targeting of IL‐17 production by T helper type 17 (Th17) and γδ T cells, while leaving that of CD49b+ natural killer (NK and NK T) cells intact, reflects the ability of helminths to modulate the immune system without immunocompromising the host. Exploiting helminth immunomodulatory mechanisms therefore offers the potential for safer therapies than current biologicals, such as 'IL‐17 blockers', that are not able to discriminate sources of IL‐17 and hence present adverse effects that limit their therapeutic potential.